STUDENTS INCREASING STUDENT VOCABULARY BY USING CROSSWORD PUZZLE EIGHT GRADE OF SMP NEGERI 1 GALANG - Jaya Jaya (Jurnal Madako Education, 2019)
The objective of the research is to prove whether the use of crossword puzzle is effective to increase students’ vocabulary. This pre-experimental study uses 23 students as a sample. They are grade VIIIc of SMP Negeri 1 Galang. The procedure of this research consists of pretest, treatment, and posttest. The result of the analysis shows that crossword puzzle contributes greatly to increse the students’ vocabulary. It can be seen by the difference of the mean score between pre-test and post-test. The mean score of pre-test is 67.30 while in the post-test increase up to 90.87. The data of this research are analyzed by using SPSS Program version 16.0. Then the data of both tests are analyzed by using T-test, and the result shows that the T-test value 8.502 is high than T-table value 2.074. It can be inferred that crossword puzzle is very effective to increase students’ vocabulary.  Keywords: Increasing, Crossword Puzzle, Vocabulary.